EVALUATING IN-FLIGHT SERVICE OF BATIK AIR USING IMPORTANCE AND PERFORMANCE ANALYSIS - Pangow, Visilia Lidyana; Massie, James D.D; Tielung, Maria V.J (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract : Transportation is the most necessary things in fast-paced era for supporting people’s daily activities. Batik Air as full service airlines should be focus on the quality of service. The aim of this study is to evaluate the importance and performance of Batik Air in-flight service. The variable used in this research are ambience of cabin, in-flight meal service, in-flight entertainment service and cabin crew service. The population of this research is all the customer of Batik Air in Manado and the sample of this research is 100 customer of  Batik Air in Manado who have ever experience its in-flight service. The analysis method that used in this research is Importance and Performance Analysis (IPA). Based on the result of IPA, tasty food, top quality ingredients, calm ambience inside cabin are plotted in quadrant I. Hygienics food, aromatic inside cabin, air temperature, flight attendant look attractive, flight attendant is patient and understanding, flight attendant provide information correctly, the polite behavior of flight attendant, friendly service from flight attendant are plotted in quadrant II, well read magazine, reasonable portion, interesting food appearance, interesting decoration, TV screen attract passenger, nice music to hear, various TV programs are plotted in quadrant III. TV facilities not difficult to use and lighting are plotted in quadrant IV. Keywords: Airline industry, Batik Air, In-flight Service, Importance and Performance Analysis.